Some things you just cannot share: On Schneider’s Law, geminates and syllables - Markoulaki, Katerina; Topintzi, Nina (Selected papers on theoretical and applied linguistics, 2023)
Various dialects of Inuktitut present consonant reduction in sequences of consonant clusters due to an alleged ban on syllable-adjacent geminates. This ban has been known as Schneider’s Law (henceforth SL). The present paper re-approaches its definition, focusing on the markedness of geminates and their co-existence in a single syllable. We claim that the underlying cause of SL lies in the fact that two geminates under a single syllable node render the syllable ‘super-marked’ thus calling for simplification of one of the two geminates. We also propose that SL is a more widespread phenomenon applying to other languages too including Japanese, Dogrib and Trukese.